2012
DOI: 10.1245/s10434-012-2579-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients after Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy: Is It Worth the Risk?

Abstract: Survivors after CRS and HIPEC have postoperative quality of life similar to preoperatively, with most of the reduced elements recovering after 6-12 months. We conclude that reduced quality of life of patients after CRS and HIPEC should not be used as an argument to deny surgical therapy to these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
48
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 24 publications
1
48
1
1
Order By: Relevance
“…A recent prospective study by Tsilimparis et al [21] showed a recovery of health-related quality of life similar to our data. This growing evidence from an increasing number of centers indicates that in this highly specialized field of oncological surgery, good results can be achieved not only in a few leading centers that may be operating in extremely favorable conditions but also in many different institutions and healthcare systems.…”
Section: Discussionsupporting
confidence: 92%
“…A recent prospective study by Tsilimparis et al [21] showed a recovery of health-related quality of life similar to our data. This growing evidence from an increasing number of centers indicates that in this highly specialized field of oncological surgery, good results can be achieved not only in a few leading centers that may be operating in extremely favorable conditions but also in many different institutions and healthcare systems.…”
Section: Discussionsupporting
confidence: 92%
“…The surgery is presumed to have a lasting negative impact on the patients quality of life. While there have been no studies that look at patients undergoing CRS and HIPEC for gastric cancer in particular, there have been numerous retrospective and prospective studies that have looked at patients undergoing CRS and HIPEC for various pathologies [69][70][71][72][73][74][75][76]. Various quality of life instruments have been used which include the EORTC and SF 21.…”
Section: Discussionmentioning
confidence: 99%
“…Many cancer treatments prolong life at the cost of significant morbidity; however, there is evidence that CRS-HIPEC may provide both morbidity and mortality benefit. This question of quality of life was also addressed by Tsilimparis et al, 64 they found patient quality of life after CRS-HIPEC to be similar to what it was preoperatively. Moreover, most measures of quality of life recovered to normal levels within 6-12 months of undergoing CRS-HIPEC.…”
mentioning
confidence: 82%
“…66 For many patients with gastric cancer, the palliative benefit and reduction in cancer morbidity with the use of HIPEC is significant. This question of quality of life was also addressed by Tsilimparis et al, 64 they found that patients undergoing CRS-HIPEC had quality of life after surgery similar to what it was preoperatively with most measures of quality of life recovering to normal levels within 6-12 months. They concluded that reduced quality of life was not an argument against denying these patients this beneficial treatment option.…”
mentioning
confidence: 87%
See 1 more Smart Citation